New classification 3 columns theory of lumbar degenerative cascade (literature review) - Darwono, Bambang; Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Lumbar degeneration is a pathologic condition in the aging spine that changes the bio-mechanic construct of the lumbar mobile segment either single or multi-levels, leading to low back pain syndrome and lead to a deformity/de novo scoliosis. The generally well accepted theory of lumbar degeneration was published by Kirkaldy-Willis, et all (1978), and clearly described the pathologic cascade of lumbar mobile segment, but only involve 2 columns: the anterior column (disc) and middle column (posterior joint/ facet). The posterior column degenerative cascade was published by Christian Ingerslev Baastrup (1933). He described about the pathologic changes on spinous processes of lumbar vertebrae and the soft tissues in between them, which was then known as Baastrup’s disease or Kissing Spine. Lacking off to understand the etiology due to a limitation of studies in histologic and radiographic changes at that time, then this theory was forgotten in the clinical practice until the recent Bristol and Auckland study, which were published in European Spine Journal (2012). Their study describes clearly the pathologic cascade of the posterior column that contributing the lumbar degeneration. Based on this 3 columns theory of lumbar degenerative cascade, then a new classification is designed to describe detail of bio-mechanic change in the anterior, middle and posterior column leading to low back pain syndrome and deformity. The justification of surgical treatment to fix and reconstruct the bio-mechanic changes of the 3 columns of lumbar mobile segment could be based on this new classification.